PENGARUH KESADARAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada Pegawai Negeri Sipil Di Lingkungan Kecamatan Putussibau Utara) - Marjono Marjono; Hermanus Dingun; Ana Yuliana (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
This study aims to analyze how the influence of tax awareness and sanctions on the compliance of taxpayers who are civil servants (PNS) in Putussibau Utara district in paying income tax (PPh). The variables and objects of this study were chosen given that PPh is the country's largest source of state revenue, the collection system uses a self assessment system and the status of civil servants as state apparatuses is expected to be an example for the public in making compliant payments and tax reporting. Using multiple linear regression analysis techniques, this study concludes that simultaneous awareness and taxation sanctions have a significant effect on taxpayer compliance, but only partially tax sanction variables have a positive effect on tax compliance. So as to maintain and improve the compliance of PNS taxpayers, it is done by implementing strict taxation sanctions and obliging to attach Tax Returns for civil servants to occupy positions and manage personnel. In addition, it is necessary to disseminate information to PNS that PNS obligation is not only to pay and report taxes from their income as PNS, but for all other income they receive, so that their awareness to pay and report taxes honestly on all their income